(untitled) (Research, Society and Development, 2021)
Objective: to describe the appropriate conducts for the management of burn patients, according to the level of assistance (pre-hospital or hospital), the severity and the particularities in the care. Methodology: This is an integrative literature review of complete articles available in the LILACS, SciELO and MEDLINE databases, using as descriptors "Burns", "Burn Units" and "First Aid", published between 2010 and 2020. After a critical analysis, 8 articles were selected according to the inclusion criteria, which comprised the final sample of the study. Results: Adequate care for burn victim patients must follow rigid and pre-established protocols, highlighting pre-hospital care with the injury, according to the type of burn that occurred, as well as continuing with the treatment of a team multiprofessional, respecting the particularities in the conduct of cases of special populations. Conclusion: The management of burn patients requires specific skills, knowledge and clinical assessment for the evolution of a better prognosis.